PERAN LUBUK LARANGAN DALAM MENINGKATKAN PENDAPATAN EKONOMI MASYARAKAT (STUDI KASUS DI DESA GUNUNG TUA JULU KABUPATEN MANDAILING NATAL) - RUKIAH, RUKIAH (2020)
This research is motivated by the existence of a hole in the ban in the village of Gunung Tua Julu, one of the villages located in Panyabungan District, Mandailing Natal Regency, which has natural potential that is still preserved until now, one of which is the hole in the ban. The river that passes from Gunung Tua Village is utilized by the community to become a Lubuk prohibited to increase their economic income. The activities under the ban are guarded and can only harvest natural products on the day or at the time determined by the community leaders. This type of research is field research, namely research activities in which the research data source is extracted directly in the field. This research shows that the process of managing lubuk prohibition of the people of Gunung Tua Julu Village is carried out with noble principles, there is mutual honesty between the committee and the participants, does not damage the environment, and there is an attitude of mutual help. In general, the role of lubuk prohibition in Gunung Tua Julu village in terms of management and economic improvement, according to the author, greatly affects long-term economic improvement. However, the existing structure for managing the lubuk prohibition of Sungai Gunung Tua Julu Village needs to be replaced periodically and renewed the roles and responsibilities of the management. It is intended that the management of prohibited fish in Sungai Gunung Tua Julu Village is more organized and structured. In the new institution, the role of prohibited fish management needs to be more activated, besides that it needs to be strengthened by the Mandailing Natal Regency Fisheries Service to make it more optimal.